Passive Acoustic Monitoring Reveals New Insights Into the Acoustic Occurrence and Foraging Activity of Hector's Dolphins in Porpoise Bay, New Zealand - Max Harvey; Stephen M. Dawson; William J. Rayment (New Zealand Journal of Marine and Freshwater Research, 2026)
To effectively mitigate disturbances from human activities on vulnerable dolphin populations, it is crucial to understand fine‐scale variation in habitat use. This study investigated the habitat utilisation of a small subpopulation of Hector's dolphins ( Cephalorhynchus hectori ) in Porpoise Bay, New Zealand. Passive acoustic monitoring was conducted from January to August 2020 using two T‐PODs deployed in the inner and middle of the bay. Generalised additive models were used to investigate the influence of time of day, tidal state, season, and site on Hector's dolphin acoustic occurrence (measured as detection‐positive minutes per hour) and foraging activity (measured as foraging click trains per hour) in the bay. Dolphin acoustic occurrence was greatest during daylight hours and around high tide, particularly in the sheltered inner bay. Foraging activity mirrored these patterns and, like acoustic occurrence, showed no significant seasonal difference. Peak foraging activity occurred in the inner bay during the morning and early afternoon, shifting toward the middle of the bay later in the day. These findings expand our understanding of the drivers of Hector's dolphin habitat use and provide new insights for managing stressors to the subpopulation that uses Porpoise Bay.

Estimating the abundance of the Hector's dolphins ( Cephalorhynchus hectori hectori ) that use Porpoise Bay, New Zealand - Max Harvey; Steve Dawson; William Rayment (New Zealand Journal of Marine and Freshwater Research, 2024)
Hector's dolphin, an endangered species endemic to the coastal waters of Aotearoa New Zealand, has a highly fragmented population structure. Low abundance of some local subpopulations, coupled with a stepping‐stone mode of gene flow, suggests that these are at high risk of extinction. During the austral summer, dolphins from the small, genetically distinct subpopulation found along the South Island's south‐east coast frequently use Porpoise Bay, an important foraging and calving area. The estimate of abundance of dolphins using the bay has not been updated since the introduction of protection measures in 2008 intended to mitigate bycatch in fisheries. Photo‐ID surveys, including random photography to estimate mark rate, were conducted during summer 2020. Using Chapman's version of the Lincoln‐Petersen estimator, it was estimated that 63 Hector's dolphins (95% CI = 46–79), including three new calves, used Porpoise Bay during the study period. While regression analyses showed no evidence of change since previous abundance estimates in 1996–97, 2002–03, and 2008, the very low estimated abundance validates fears for the long‐term persistence of this subpopulation. In this context, potential threats need to be managed within a precautionary framework, with a clear goal of facilitating recovery.